Competitiveness of the Polish economy compared with the Romanian one - Wioletta WEREDA; Alina HAGIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Generally, competitiveness of the economy defines importance of the nationaleconomy in the world market. It is a very complex notion assessed by variousinstitutions using different indicators which actually reflect only selected aspects, suchas prospects for economic development, technological progress, quality of publicinstitutions, quality of the national business environment, quality of business legislation,level of prices as well as technical infrastructure.